2001
DOI: 10.1097/00012272-200103000-00003
|View full text |Cite
|
Sign up to set email alerts
|

They Took the Time … They Started To Care: Stories of African-American Nursing Students in Intercultural Caring Groups

Abstract: Socially responsible nurse educators articulate the need to explore opportunities for nursing students to participate in experiences that promote caring and respect for diversity. This research illuminates the experiences of 10 African-American nursing students who participated in caring groups while enrolled in a predominantly White nursing education program. Although the meanings embedded in the African-American students' stories revealed commonalities with those of European-American and international studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Creating learning communities where students use the safe space established by the teacher decreases barriers such as isolation and anxiety. These experiences have been found to be specifically poignant for students of color (Kosowski & Grams, 2001;Love, 2010;McQueen, Shelton, & Zimmerman, 2004). Interconnectedness is a philosophy of bringing together a class to learn from one another and to value differences by applying them toward a common goal.…”
Section: Interconnectednessmentioning
confidence: 99%
“…Creating learning communities where students use the safe space established by the teacher decreases barriers such as isolation and anxiety. These experiences have been found to be specifically poignant for students of color (Kosowski & Grams, 2001;Love, 2010;McQueen, Shelton, & Zimmerman, 2004). Interconnectedness is a philosophy of bringing together a class to learn from one another and to value differences by applying them toward a common goal.…”
Section: Interconnectednessmentioning
confidence: 99%
“…Mentoring is important in that it seeks to develop an ongoing faculty-student relationship in which the student can receive academic advisement, career development, and employment networking assistance. Faculty support is another facilitating theme cited in the literature (Campbell, & Davis, 1996;Dowell, 1996;Kosowski, Grams, Taylor & Wilson, 2001;Rew, 1996). However, additional research is needed to identify what behaviors are most supportive for the Hispanic/Latino student and whether there is a difference in support as expressed from minority or majority faculty members.…”
Section: Retention-strategiesmentioning
confidence: 99%
“…[2,3,25,30,31] The story of the importance of bonding and giving and receiving support from caring group members remains an important piece of the Caring Group experience. For example, previous research revealed an important component of the Caring Group experience as giving and receiving personal and academic support, [2] which is also evident in this study.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…[2,15,16] The creation of caring groups in nursing programs was an additional example of a strategy to teach caring within nursing education, and these group experiences were declared effective in increasing students' perception of caring behaviors from faculty. [2][3][4][5][6] A caring curriculum in Taiwan utilized caring groups as a way for teaching and learning caring. [4,5] Research related to these caring groups indicated that "the results showed that with appropriate curricula and learning strategies, caring skills may be learned".…”
Section: Caring In Nursing Educationmentioning
confidence: 99%
See 1 more Smart Citation